Analysis of the Influence of Financial Performance, Firm Age, and Financial Classification on Financial Reporting Quality Through Good Corporate Governance - Orlin Cicilia (Journal Research of Social Science, Economics, and Management, 2026)
Financial reporting quality (kualitas pelaporan keuangan) becomes an important aspect for stakeholders, especially for investors. Financial reporting quality will emerge when a company has good financial performance, a long existence in the marketplace, a healthy financial classification, and diligent implementation of good corporate governance. The purpose of this research is to analyze the effect of financial performance, firm age, and financial classification on financial reporting quality through good corporate governance as a moderating variable. The sample used for this research consists of LQ 45 companies listed on Bursa Efek Indonesia from 2017 to 2019. The hypothesis test used for this research is multiple regression analysis involving a moderating variable (moderated regression analysis). The results of this research show that firm age (X2) has an influence on financial reporting quality (Y), and good corporate governance (Z) also has an influence on financial reporting quality (Y).